2008
DOI: 10.1073/pnas.0802493105
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of the nuclear cap-binding complex and SERRATE in pre-mRNA splicing and microRNA processing in Arabidopsis thaliana

Abstract: The processing of Arabidopsis thaliana microRNAs (miRNAs) from longer primary transcripts (pri-miRNAs) requires the activity of several proteins, including DICER-LIKE1 (DCL1), the double-stranded RNA-binding protein HYPONASTIC LEAVES1 (HYL1), and the zinc finger protein SERRATE (SE). It has been noted before that the morphological appearance of weak se mutants is reminiscent of plants with mutations in ABH1/CBP80 and CBP20, which encode the two subunits of the nuclear cap-binding complex. We report that, like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
432
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 365 publications
(459 citation statements)
references
References 67 publications
17
432
0
10
Order By: Relevance
“…In addition, SE may also act as a transcription mediator (Voisin et al, 2009). By analysis of public tiling array data sets, we found that se-1, se-3, cbp20-1, and cbp80-285 indeed accumulated higher levels of pri-miRNAs compared with the wild type (see Supplemental Figure 14 online), confirming previous results (Laubinger et al, 2008). Moreover, we found a global increase of lincRNA expression levels in these four mutants (see Supplemental Figure 14 online) with the following order of severity: cbp20, se-3, se-1, and cbp80.…”
Section: Se Cbp20 and Cbp80 Regulate Lincrna Biogenesissupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, SE may also act as a transcription mediator (Voisin et al, 2009). By analysis of public tiling array data sets, we found that se-1, se-3, cbp20-1, and cbp80-285 indeed accumulated higher levels of pri-miRNAs compared with the wild type (see Supplemental Figure 14 online), confirming previous results (Laubinger et al, 2008). Moreover, we found a global increase of lincRNA expression levels in these four mutants (see Supplemental Figure 14 online) with the following order of severity: cbp20, se-3, se-1, and cbp80.…”
Section: Se Cbp20 and Cbp80 Regulate Lincrna Biogenesissupporting
confidence: 89%
“…To confirm this finding, we analyzed nine tiling array data sets obtained from different experiments performed by various groups (Laubinger et al, 2008(Laubinger et al, , 2010Zeller et al, 2009). Again, similar expression patterns appeared in all nine independent experiments that used various tissues and different stress treatments (see Supplemental Figure 9 online).…”
Section: The Majority Of Lincrnas Are Expressed At Levels Between Thomentioning
confidence: 63%
See 3 more Smart Citations